Can the use of proprioceptive knee braces have implications in the management of osteoarthritic knees: An exploratory study. (April 2019) - Kwaees, Tariq A; Richards, Jim; Rawlinson, Gill; Charalambous, Charalambos Panayiotou; Chohan, Ambreen
Background: Use of proprioceptive knee braces to control symptomology by altering neuromuscular control mechanisms has been shown in patellofemoral pain. Although their potential in patients with knee osteoarthritis is vast, little research has examined their efficacy. Objectives: This study examines the effect of a proprioceptive knee brace on lower limb kinematics and kinetics in healthy participants and in participants with OA. Methods: Thirteen healthy participants were asked to perform a 10-cm step-down task with and without a proprioceptive brace. Data were collected using a 10-camera Qualisys system. Individuals with osteoarthritis completed the Knee injury and Osteoarthritis Outcome Score before and after 4 weeks of intervention. Results: During step-down reductions in knee maximum internal rotation, transverse range of movement, transverse plane angular velocity and maximum internal rotation angular velocity was seen. Ankle plantar flexion and inversion angular velocity decreased while inversion and maximum supination angular velocity increased. Improvements in Knee injury and Osteoarthritis Outcome Score were noted across all parameters with brace use. Conclusion: Positive changes in kinematic variables in multiple planes can be achieved with proprioceptive bracing alongside improved patient outcome. These changes occur at the knee but analysis of other weight bearing joints should not be overlooked in future studies. This study supports the concept of neuromuscular reinforcement and re-education through proprioceptive bracing and its application in the management in knee osteoarthritis. Clinical relevance: Proprioception can alter symptoms and biomechanics embraced and adjacent lower limb joints. The results of this study highlights the potential uses of non-mechanical bracing in the treatment of osteoarthritis and other potential to bridge the osteoarthritis treatment gap. Furthermore, large-scale research is needed to match disease subset to brace type.